EFFECTIVE METHODS FOR REDUCING PREGNANCY-RELATED ANXIETY IN THE THIRD TRIMESTER: A SYSTEMATIC REVIEW - Rahayu, Nova Avianti; Putri, Rizkiana; Paramitha, Intan Azkia (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
During pregnancy, mothers often feel fear, worry, and anxiety. This anxiety can have adverse effects on both the mother and the baby, such as increased maternal mortality, preterm birth, and cognitive issues. To address this, a study was conducted to identify ways to reduce anxiety in third-trimester pregnant women. This study used a systematic review method to find the most effective health interventions, as obtained from several articles. Through a systematic review of various health interventions following PRISMA 2020 guidelines, 11 articles were analyzed. The findings suggest that methods like prenatal yoga, virtual reality, and music can effectively alleviate anxiety during childbirth. Overall, the study concludes that there are several effective ways to help pregnant women in their third trimester manage anxiety related to labor. The findings suggest that methods like prenatal yoga, virtual reality, and music can effectively alleviate anxiety during childbirth. Overall, the study concludes that there are several effective ways to help pregnant women in their third trimester manage anxiety related to labor.